Narratology in Early Modern Medical Manuscripts: The Case of London, Wellcome Library, MS 213 - Esteban-Segura, María Laura (Universitat Jaume I, 2023)
It has been argued that narrative elements can be found throughout the history of English scientific writing. Narratives can be linked to specific genres; thus, learned texts for medical doctors were different from those directed to lay audiences (Taavitsainen, 2022). This article sets out to analyse a specific type of medical narrative, that of recipe collections, focusing for the purpose on the text housed in London, Wellcome Library, MS 213. The manuscript dates from the beginning of the seventeenth century (1606, more specifically) and gathers recipes “experienced and tryed by the speciall practize of Mrs Corlyon” (Moorat, 1962-1973). The codex belonged to Alethea Howard (née Talbot), Countess of Arundel. The main aim of the study is to identify and examine narrative forms and functions as well as particular features in the collection of recipes held in MS Wellcome 213, which can contribute to the knowledge of recipes written by and for women during the early modern period.
Keywords: Medicina - Manuscritos; Early Modern English; medicine; MS Wellcome 213; recipe collection; women writing